1989
DOI: 10.1016/0304-3959(89)90182-6
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the construct validity of the McGill Pain Questionnaire

Abstract: In order to circumvent problems with self-report measures of pain we conducted an experimental analysis of MPQ pain descriptors using a Stroop task. In this task subjects are asked to name the colours in which stimulus words are written. Previous research has demonstrated that words with emotional significance interfere (indexed by increased latencies to respond) with a person's ability to name the colour. We predicted that: (1) chronic pain patients, compared with normal controls, would show more interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 13 publications
3
85
1
1
Order By: Relevance
“…It has been recently shown that individuals who are highly pain-sensitive, as measured by experimental pain sensitivity, are also attentionally more engaged with pain-related stimuli, (Baum et al, 2011). In a classical Stroop task (Pearce & Morley, 1989), highly pain-sensitive people were slower than less pain-sensitive subjects in naming the color of the words when they were presented with pain-related stimuli, thus showing an attentional bias towards pain-related information.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that individuals who are highly pain-sensitive, as measured by experimental pain sensitivity, are also attentionally more engaged with pain-related stimuli, (Baum et al, 2011). In a classical Stroop task (Pearce & Morley, 1989), highly pain-sensitive people were slower than less pain-sensitive subjects in naming the color of the words when they were presented with pain-related stimuli, thus showing an attentional bias towards pain-related information.…”
Section: Discussionmentioning
confidence: 99%
“…There is very little research that directly examines hypervigilance in pain patients who report pain-related fear. Based on their study investigating the construct validity of the McGill pain questionnaire, Pearce and Morley (1989) suggested that patients with chronic pain are characterized by selective attention towards cues that are thematically related to pain and its consequences. A more recent replication with the dot-probe paradigm, Asmundson et al (1997) found that individuals with chronic pain with low anxiety sensitivity were able to shift their attention away from stimuli related to pain, in contrast to the subjects with high pain sensitivity.…”
Section: Attention To Bodily Sensationsmentioning
confidence: 99%
“…In the modified Stroop version, the color words are replaced by emotionally valent, often threat related, words and neutral words [161]. In pain research, the threat-related words consist of pain-related words [116]. Participants are instructed to identify as fast as possible the color of the word, while ignoring the meaning of the word.…”
Section: Meta-analytic Proceduresmentioning
confidence: 99%
“…Pain researchers have typically adopted hypotheses and paradigms from psychopathology research. In the first study on this topic, Pearce and Morley (1989) adapted the modified Stroop task, and presented pain patients with cards containing colored words [116]. They instructed participants to name the color of the words while ignoring word meaning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation